Dynamics of optical solitons and conservation laws of a new (2+1)-dimensional integrable nonlinear evolution equation in deep water oceanic waves - Singh, Sudhir; Sakthivel, R.; İnç, Mustafa; Yusuf, A.; Murugesan, K. (World Scientific Publ Co Pte Ltd, 2020)
An integrable extension of the famous Schrodinger equation in (2+1) dimension, named Kundu-Mukherjee-Naskar (KMN) equation, governing the evolution of ion-acoustic wave in magnetized plasma and oceanic rogue waves is considered, and dark/black as well as gray optical soliton solutions are constructed by using a complex envelope ansatz approach with appropriate conditions for the existence of solitons. Also, a new class of combined gray and black optical soliton solutions is obtained by applying Chupin Liu's theorem, and it is found to be anti-dark solitons. Additionally, Gaussian wave solutions are derived. Further, the investigation of symmetry analysis, nonlinear self-adjointness and conservation laws (Cls) for the KMN equation are carried out. These results further enrich and deepen the understanding of the dynamics of a higher-dimensional soliton propagation.
Keywords: Optical solitons; conservation laws; Kundu-Mukherjee-Nasker equation; complex envelope ansatz solution; Chupin Liu's theorem